MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR SISWA MATERI BERBAGAI SUMBER ENERGI DAN MANFAATNYA DENGAN METODE DEMONSTRASI KELAS IV SEKOLAH DASAR NEGERI CONEGARAN TAHUN PELAJARAN 2016/2017 - Sukisrofil Janah (Universitas PGRI Yogyakarta, 2018)
Given the importance of education in Indonesia for the intellectual life of the nation, this classroom action research aims to improve ongoing learning and improve teacherperformance. With the demonstration method, it is expected that students can improve theiractivity and achievement in the class on the material of various energy sources and itsbenefits. The implementation of this class action is carried out in two stages: first cycle andsecond cycle. The first cycle was held on April 11, 2017 and the second cycle was held onApril 25, 2017. The results obtained in each cycle I experienced a significant increase. In thefirst cycle of students' activity increased from 50% to 52.58% or 8 of 15 students who areactive in learning. Student achievement also mangalami increase that reaches 60% andaverage - class average reach 76. In cycle II student activity more increase become 76,2% or13 from 15 student active in learning. Student achievement has increased the average grade to85.33. It turned out that by using the demonstration method, students' activeness and studentachievement on the material of various energy sources and its benefits can increase.Keywords: liveliness, learning achievement, demonstration method